Physical activity, well-being and needs satisfaction in eight and nine-year-old children from areas of socio-economic disadvantage. Issue 3 (3rd July 2017) - Breslin, Gavin; Shannon, Stephen; Fitzpatrick, Ben; Hanna, Donncha; Belton, Sarahjane; Brennan, Deirdre
ABSTRACT: Need-supportive environments have been shown to predict children's physical activity levels, and in a few cases to well-being. Grounded in self-determination theory (SDT), this cross-sectional study aimed to determine the influence of psychological need (competence and social relatedness) satisfaction on physical activity levels and well-being in children from areas of social and economic disadvantage. A total of 211 children aged eight and nine years from areas of low socio-economic status wore an accelerometer for one week, and completed a questionnaire assessing psychological need satisfaction and well-being. Confirmatory factor analysis and path analysis were conducted to assess the factor structure of the measures, and to test for theoretical relationships between psychological needs, physical activity and well-being. The factor structure of the instruments was supported, and a significant positive relationship was found between athletic competence and physical activity ( β  = 0.19). Athletic competence ( β  = 0.19), along with parental relatedness ( β  = 0.32), positively predicted children's well-being. Physical activity alone did not predict well-being. Based on these findings, practitioners may consider components of SDT, reflective of need-supportive environments, when designing physical activity interventions. Interventions aimed at supporting children's perceptions of competence, and the involvement of parents, may offer the opportunity to increase well-being.